111k views
1 vote
4n-6 (n - 2) = -24 + 7n
O No Solutions
O All Real Numbers
O n = 4
O n = 2.9

User Goldberg
by
5.2k points

1 Answer

2 votes
N=4

4n-6 (n-2) = -24 + 7n

You first multiply the six with the equation in the parentheses making it:

4n-6n + 12= -24 + 7n

You then subtract 4n from -6n changing it to:

-2n + 12 = -24 + 7n after that you switch the 12 and 7n so that the equation can be

-2n -7n = -24 - 12

After that combine the numbers together:

-9n = -36

Then divide both sides by -9 making

n= 4
User Edvinas
by
5.4k points